cover

On Friday I posted this puzzle:

How can you express the number 100 using six nines and no other digits?

If you have not tried to solve it, have a go now. For everyone else the answer is after the break.

99  99/99

Did you solve it? Any other solutions?

I have produced an ebook containing 101 of the previous Friday Puzzles! It is called PUZZLED and is available for the Kindle (UK here and USA here) and on the iBookstore (UK here in the USA here). You can try 101 of the puzzles for free here.

46 comments

  1. I think there’s a plus sign missing in Richard’s solution
    and I’m now awaiting all the other solutions.

    I also had 99.9999 (recurring)
    and 99+99/99 and (9/9)*(9/9)+99

    and I know there were some [other] good ones

    1. Lord Manley,
      Great to hear that you went with that one. Are you now in a position to elaborate on your two answers to Richard’s puzzle of 6th December when you commented “I have one which requires capitals and one which does not.”?

  2. No plus sign missing, it is an expression of a single number: ninety-nine and ninety-nine ninety-ninths, not 99+99/99. Simply a limitation of the medium.

    1. I don’t see a plus sign in Richard’s piece at the top. It doesn’t make those that used + or * wrong, it is simply another answer.

    2. I would argue that a mixed number is not properly formed unless the fractional part is strictly less than 1.

  3. 11 using only +, —, * and /

    99+(99/99)=100 <This was my almost instantaneous answer
    (9+9/9)*(9+9/9)=100
    (9*9)+9+9+(9/9)=100
    99-9+9+(9/9)=100
    99*(9/9)+(9/9)=100
    [99+(9/9)]*(9/9)=100
    99+(9*9)/(9*9)=100
    (99+9/9)+(9-9)=100
    (99/9)*9+(9/9)=100
    (99+9/9)/(9/9)=100
    (999-99)/9=100

    Plus another 17 using √ and ^

    99+(9^9/9^9)=100 (i.e. 99+99/99)
    (9+√9/√9)*(9+9/9)=100
    (9+√9/√9)*(9+√9/√9)=100
    (9*9)+9+9+(√9/√9)=100
    99-9+9+(√9/√9)=100
    99+(√99/√99)=100
    99*(√9/√9)+(9/9)=100
    99*(9/9)+(√9/√9)=100
    99*(√9/√9)+(√9/√9)=100
    [99+(√9/√9)]*(9/9)=100
    [99+(9/9)]*(√9/√9)=100
    [99+(√9/√9)]*(√9/√9)=100
    (99+√9/√9)+(9-9)=100
    (99/9)*9+(√9/√9)=100
    (99+√9/√9)/(9/9)=100
    (99+9/9)/(√9/√9)=100
    (99+√9/√9)/(√9/√9)=100

    1. I’m genuinely surprised to say that I understand that, Geodetective! I didn’t think I’d ever remember GCSE And A Level Maths! Thanks.

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out /  Change )

Google+ photo

You are commenting using your Google+ account. Log Out /  Change )

Twitter picture

You are commenting using your Twitter account. Log Out /  Change )

Facebook photo

You are commenting using your Facebook account. Log Out /  Change )

w

Connecting to %s